Response Quality of Self-Administered Questionnaires: A Comparison Between Paper and Web Questionnaires. (April 2014) - Rada, Vidal Díaz de; Domínguez-Álvarez, Juan Antonio
The objective of this article is to analyze the quality of the information collected by a self-administered survey addressed to citizens of Andalusia, who were offered the possibility of answering using the post or Internet. The study showed the advantages of using web-based self-administered questionnaires. Web surveys showed a low number of unanswered questions, more detailed answers to open questions, and longer answers to questions than those generated from paper questionnaires. The five open questions with text showed longer answers from the web survey, around 63 characters more. In the open questions with numerical answers, the use of drop-box (select list) generated better response than the use of a blank space left in the paper questionnaire.